Professional Competence and Computer Literacy in e-age, Focus on Healthcare - Štepánková, O.; Engová, D. (Methods of Information in Medicine, 2006)
Objectives: The healthcare sector is facing an enormous acceleration due to the emergence of new knowledge, drugs, devices and diseases. Professional competence, continuing education, service excellence and patient benefits can be facilitated by the developments in information and computer technology – computer literacy is becoming imperative for all who are involved in healthcare delivery. The paper attempts to identify solutions that can aid the process of ICT uptake for full benefit of patients and healthcare professionals.Methods: With the support of published literature, the article considers the importance of ICT skills in general and in healthcare and presents some advantages of generic vendor-independent methods of ICT certification.Results: Discussed are the preliminary results of the United Kingdom’s National Health Service information technology reform which addresses the need for intensified use of ICT and applies the ECDL concept.Conclusions: It is useful to complement the introduction of computer literacy as a qualification concept by a standardized accreditation of ICT skills. Solid level of computer literacy creates a reliable and efficient background for everyday activities of healthcare professionals, enables the application of further domain-specific training modules and prepares suitable environments for the introduction and acceptance of new technologies such as electronic health records and electronic transfer of prescriptions by positively transforming the attitudes of users towards them.
Keywords: Computer literacy; professional competence; continuing education; delivery of health care